Bioindication for ecosystem regeneration towards natural conditions: the BERN data base and BERN model - Schlutow, Angela; Kraft, Philipp; Scheuschner, Thomas; Schlutow, Mark; Schröder, Winfried (Universität Vechta, 2024)
The primary task of the BERN database is to document reference data on typical site parameters for the occurrence of plant communities in which their diagnostic species are in competitive equilibrium with each other and in homeostatic equilibrium with the site factors. Common approaches for the creation of a site-plant database such as ordination or bioindication based on individual species like PROPS or MultiMOVE model are of limited use because it is not possible to determine the potential occurrence of a plant species on the basis of site factors, since the competitive influences cannot be determined in advance according to current knowledge. Therefore, the BERN database takes into account the structure of plant communities with the abundance and dominance of species in the competitive equilibrium of plant communities as a reference for determining anthropogenically induced changes. Qualitative knowledge on the relationship between site types and vegetation communities is widely available, as can be seen from the extensive phytosociological publications. For this purpose, synoptic tables and their location descriptions of around 50,000 relevés were evaluated. The BERN database includes currently 887 central European plant communities and links to their diagnostically defining species composition. The database defines the niche of 2210 central European plant species for the soil properties pH, base saturation, carbon to nitrogen ratio, and wetness index and the climatic properties continentality, length of vegetation period, solar radiation and climatic water balance. The BERN model recombines the realised species niches that mainly form the competitively homeostatic structure of a plant community in order to determine the fundamental multifactorial niche of this community. The BERN database contains mainly historical recordings of more or less undisturbed sites. The BERN model (Bioindication for Ecosystem Regeneration towards Natural conditions) as an application module of the BERN database was developed to integrate ecological cause-effect relationships into studies on environmental status assessment and forecasting. The BERN database now has been published for the first time. The methodology of creating the BERN database and the BERN model are documented and applications are demonstrated with examples. The freely available database should invite you to supplement and modify it.
Keywords: BERN database; BERN model; Bioindication; Plant community; Effects of air pollutant inputs on biodiversity; Effects of climate change on biodiversity; Geschichte und Geografie::910 Geografie, Reisen::910 Geografie, Reisen